LOCAL WISDOM OF KINSHIP SYSTEM IN REMOTE AND ISOLATED COMMUNITIES ACCORDING TO CUSTOMARY LAW ON ENGGANO ISLAND - Andry Harijanto; Subanrio Subanrio; Hamdani Ma'akir; Joko Susetyanto (Bengkoelen Justice : Jurnal Ilmu Hukum, 2022)
The purpose of the study is to explain and describe the local wisdom of the kinship system in remote and isolated communities according to customary law on enggano island. Research methods using qualitative approaches and legal anthropology. Data collection techniques are observation, in-depth interviews and secondary data collection. The determination of informants is carried out purposively, that is, key informants are determined by the researchers themselves based on considerations of adequate education, position, and experience. Data analysis is qualitative, which is carried out continuously from the beginning to the end of the study. The results of the study were: (1) tribal groups and tribal branches; (2) traditional settlement patterns; and (3) traditional leadership systems.